The Management of retropharyngeal abscess in adult patient - Hendrayani, Anak Agung Ayu Sri Vemi; Nalle, Tince Sarlin (PERHATI-KL, 2025)
Background: Retropharyngeal abscess is an infection of the inner neck that mostly occurs in the pediatric population, although they can also arise in adults. While numerous resources discuss the diagnosis, treatment, and complications of retropharyngeal abscess in children, there is a scarcity of information available concerning its manifestation in adults. Purpose: To study the disease course, and management of retropharyngeal abscess in adults. Case report: A 41-year-old female patient came with chief complaints of difficulty of swallowing, snoring while sleeping, shortness of breath, and weight loss. These complaints had been going on for about 3 months. Clinical question: What is the management and overall disease course of retropharyngeal abscess in adult? Method: The literature search was conducted through Google Scholar, PubMed, and manual searches of e-books. Result: Thirteen articles concerning retropharyngeal abscess were found, but only 4 literatures were relevant to clinical question and inclusion criteria. Conclusion: Retropharyngeal abscess may present with a variety of symptoms. Management for retropharyngeal abscess in adult patient includes abscess incision and drainage, along with medication administration